2005
DOI: 10.1016/j.ccr.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxic microenvironment of the skin contributes to Akt-mediated melanocyte transformation

Abstract: Constitutive activation of Akt characterizes a high percentage of human melanomas and represents a poor prognostic factor of the disease. We show that Akt transforms melanocytes only in a hypoxic environment, which is found in normal skin. The synergy between Akt and hypoxia is HIF1alpha mediated. Inhibition of HIF1alpha decreases Akt transformation capacity in hypoxia and tumor growth in vivo, while overexpression of HIF1alpha allows anchorage-independent growth in normoxia and development of more aggressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 67 publications
4
154
0
1
Order By: Relevance
“…31,32 HIF1A, in particular, is largely expressed in human neoplasia, including melanomas, and is linked with metastasis 33,34 and melanocyte transformation, in conjunction with the Akt gene. 35 Furthermore, HIF1A is actively involved in triggering autophagy, a major intracellular pathway promoting the survival of tumor cells under oxygen and nutrient deprivation. [16][17][18] This autophagic process has been documented in human melanomas as early as 1982 by Horikoshi et al, 36 and melanoma cells are known to induce autophagic activity with perinuclear expression after being irradiated with UV light.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 HIF1A, in particular, is largely expressed in human neoplasia, including melanomas, and is linked with metastasis 33,34 and melanocyte transformation, in conjunction with the Akt gene. 35 Furthermore, HIF1A is actively involved in triggering autophagy, a major intracellular pathway promoting the survival of tumor cells under oxygen and nutrient deprivation. [16][17][18] This autophagic process has been documented in human melanomas as early as 1982 by Horikoshi et al, 36 and melanoma cells are known to induce autophagic activity with perinuclear expression after being irradiated with UV light.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to acquire a proliferation advantage, melanocytes expressing mutated c-Kit require a tissue-specific environment in vivo allowing activation of HIF-1a, such as hypoxia. The presence of a mild hypoxic environment in the skin has already been described (Bedogni et al, 2005), but it remains to be determined whether hypoxia is elevated in the skin located at the extremities of the hands and feet or in the mucosa where acral and mucosal melanoma develop. This strict dependency of c-Kit mutants on the microenvironment could explain the low frequency of c-Kit mutations in cutaneous melanoma (around 2%) Beadling et al, 2008).…”
Section: D576pmentioning
confidence: 99%
“…c-Kit mutants cooperate with HIF-1a to transform melanocytes Although constitutive Akt is not able to transform melanocytes in normoxic conditions (Bedogni et al, 2005) and N Dumaz, unpublished data), it has recently been shown that it can transform melanocytes in a hypoxic environment and that the synergy between Akt and hypoxia is HIF-1a mediated. To investigate the role of hypoxia in melanocyte transformation by c-Kit mutants, we grew melanocytes expressing WT c-Kit or D576 c-Kit in hypoxic conditions and measured the effect on signaling pathways and proliferation.…”
Section: D576pmentioning
confidence: 99%
“…13,14), and the timing of HIF-1a inhibition, more active in early rather than late tumor growth (15). Because HIF-1 has not been directly implicated in oncogenic transformation, although evidence has been provided that it can cooperate with AKT in melanomagenesis (16), it has been difficult to translate results from in vitro studies to animal models. Such controversial results reflect, at least in part, the complexity of the involvement of HIF-1 in human cancers and the known limitations of experimental animal models.…”
Section: Introductionmentioning
confidence: 99%